An Exploration of Environmental Practices in the Hospitality Industry. Evidence from Hotels in Addis Ababa, Ethiopia - LAMMI, D. K.; TESFAYE, Z. (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
Hotels create unforeseen damages to the environment by depleting natural resources and driving out wastes. Studies have rarely been conducted to investigate the nexus between hotels and the environment in Ethiopia. This study aims to explore environmental practices among Addis Ababa hotels. The quantitative research design was applied to the study. The data were gathered through a self-administered questionnaire and analyzed through descriptive statistics. The totels' environmental practice indicators were examined under the themes of water-saving, energy-saving, green purchase, and waste management. Within these themes, the installation of energy-efficient bulbs, installation of a key card for light; using energy-efficient appliances; regular maintenances of water and electric facilities; the installing of dual toilet and other low flow water technologies; placing of dustbins; sorting and disposing of solid wastes, and buying of local products were implemented to a certain extent. The study implicates the requirement of intervention to make hotel operation environmentally sustainable.